Proposal for a clinical skills training on the stages of the Program for General Community Medicine Doctors - Esteban Sánchez Martínez; Rubén Darío García Núñez; María Luisa Quintana Galende; César Mustelier Fernández; Israel Díaz Roig; María Aurelia San Juan Bosch (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Background: the New Medical Training Program in Cuba and Venezuela uses different scenarios of the profession to develop the teaching-learning process from the initial years of the race. Objective: to determine the invariants of skills students should acquire during their rotation by each of them, according to the degree of feasibility that each stage offers. Methods: teaching the National decided to form a work team composed of specialists in internal medicine, general medicine and other specialties of several years of experience in secondary and primary care, both in Cuba and Venezuela, who conducted several sessions group work and individual research. For its determination took into account the following aspects: a review of the curriculum to meet the health problems it faces the Comprehensive Community Health and the level of performance to be achieved in each of them, prevalence and morbidity of problems health in different scenarios, emergency medical condition of some of the health problems were also reviewed other relevant policy documents. Results: we identified the skills to develop in the hospital sector in the different functions: administrative, teaching, educational, research, and clinical care. Conclusions: defined clinical skills relevant to the role of comprehensive medical care to be developed by a graduate of the career of community medicine and the educational scenario in which they acquire and develop these.